The Role of Islamic Culture in Shaping Social Behavior in Contemporary Urban Muslim Society - Ais Isti’ana; Anggraini Pratiwi; Nadia Eka Sauwitri; Salsabila Ariyani; Istiqomah (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2025)
This study explores the significant role of Islamic culture in shaping the social behavior and moral frameworks of contemporary urban Muslim societies, particularly in Indonesia. Drawing from a qualitative research approach, including interviews, observations, and literature review, the study investigates how key Islamic values such as mutual respect (ta’awun), honesty (sidq), modesty (haya’), and social responsibility are integrated into daily life despite the influence of secular modernity. The findings show that Islamic culture remains deeply embedded in the lives of urban Muslims, impacting their interactions within families, neighborhoods, and workplaces. Islamic cultural practices not only preserve moral values but also adapt to modern societal challenges, offering a stable framework for individuals and communities. Moreover, the study highlights how these values contribute to social resilience, the formation of ethical identities, and the integration of Islamic principles with the demands of urban, digital, and globalized contexts. The research underscores the adaptive nature of Islamic culture as it negotiates the balance between tradition and modernity, demonstrating its continued relevance in promoting social harmony and ethical conduct. The study suggests that Islamic culture is not merely a religious or static tradition but a dynamic force that shapes behavior, fosters community cohesion, and guides moral decisions in contemporary Muslim societies.